The Effectiveness of Islamic Educational TikTok Content by @bachrulalam in Enhancing Adolescents’ Interest in Learning Arabic - Alfath Akhamanuddin Rabbani Raharja; Hilalludin Hilalludin (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study explores the effectiveness of TikTok content created by the account @bachrulalam in enhancing adolescents’ interest in learning Arabic, within the framework of Islamic education. The study aims to examine how digital religious content can motivate youth to engage with Arabic, a language central to understanding the Qur’an and Hadith. Using a qualitative descriptive method with a case study approach, data were collected through non-participant observation of selected TikTok videos, semi-structured interviews with ten teenage users, and analysis of audience interactions in the comment sections. The findings reveal that @bachrulalam’s content significantly boosts motivation by integrating Islamic values with modern, relatable digital formats. His casual and engaging delivery, coupled with the inclusion of Arabic script, transliteration, Indonesian translations, and practical usage in daily Islamic phrases, makes Arabic learning more approachable. Additionally, features like short video formats, interactive discussions, and creator responsiveness support an inclusive digital learning environment. Viewed through Social Learning Theory, the study finds that adolescents engage in observational learning, imitating pronunciation and usage patterns presented in the videos. In conclusion, TikTok-based Islamic educational content holds strong potential as a complementary tool to formal Arabic instruction. This study underscores the importance of collaboration between Islamic educators, content creators, and religious institutions in developing innovative Arabic learning strategies for the digital era.